MORPHOLOGICAL AND ANATOMICAL STUDY OF GRANULES WITH SEEDS EPIDERMIS OF PLANTAGO OVATA FORSSK - J. V. Daironas; I. N. Zilfikarov; V. V. Vandyshev; E. A. Miroshnikova (Фармация и фармакология (Пятигорск))
The results of a morphological and anatomical study of granules from the epidermis of Plantago ovata seeds are presented in the article. Morphological and microscopic diagnostic signs are important for establishing the authenticity of medicinal plant material and drugs made from it.The aim is the identification of morphological and microscopic diagnostic characteristics of the seed epidermis of Plantago ovata, minimal and sufficient to establish the authenticity of the granular pieces of the plant’s epidermis.Materials and methods. The study of morphological and anatomical characteristics as well as histochemical study were conducted according to the procedures of the State Pharmacopoeia of the Russian Federation XIII edition. Microscope “Micromed-1” and digital camera MD300 Electronic Eyepiece (Jincheng) were used. Photos were edited in Adobe Photoshop CS6.Results and discussion. Morphological signs of the epidermis of Plantago ovata seeds include its light yellow or pinkish-yellow color and a presence of a pigmented spot of pink or light brown color on the epidermis of the convex side of the seeds and along the seed. These signs are applicable for diagnosis and are also found in crushed raw materials. Granules are rough lumps, consisting of stuck together epidermis pieces. They are characterized by a yellowish or light brown color and the presence of a pigmented spot. The microscopic diagnostic signs include the structure of the upper and lower epidermis, the presence of cells with mucus and starch grains. The upper epidermis consists of large polygonal cells with straight thin anticlinal walls. The cells are covered with a smooth cuticle and are filled with mucus. The lower epidermis consists of elongated rectangular cells. Cells with mucus swell rapidly in the radial direction. Biometric characteristics of anatomical diagnostic signs were established.Conclusion. As the result of a morphological and anatomical study the diagnostic signs of the raw material and granules of Plantago ovata seed husks were established. The structure of epidermal cells filled with mucus, starch grains and the presence of fragments of the inner pigment layer of the skin and endosperm belong to them. The obtained results are consistent with the literature data. It can be used in the development of a normative document for granules of Plantago ovata seed husks.